ECONOMIC ANALYSIS FOR PRODUCING MASS LEAVES AND VOLATION OIL OF LEMON GRASS PLANT AND ITS PHARMACEUTICAL PARTICIPATION - Adnan Ahmed Thalaj (Mesopotamia Journal of Agriculture)
This study contained the range of suitability of environmental conditions of the city of Samarah in planting cymbopogoncitratus (DC) which is called Lemon Grass (West Indiana Type) in the General Firm for pharmaceutical industries inorder to produce this plant locally and providing volatile oil extracted from it as a natural raw material for pharmaceutical industries . The study included Also, the economic avail to establish the project in which it is characterized by high demand on its outputs from the company . There was a sort of dependence on the value of company’s import (SDI) of the raw material Nystation as a basis for knowing the size of local demand throughout studying the market . It was clear through that the study the basic aspect practiced upon the plant to prepare and analyze the project and its compatibility with the environmental conditions for the city of Samarah to produce the plant . We were able to get four monthly cultivars of the plant and oil quantity was 15 liters per hectare for the first year and the production increased later to reach 39 liters per hectare . The basic tests made upon the plant have shown a high competency to use it in pharmaceutical industries for it retard the growth of Somany fungis which cause human, plant and animal diseases and this is more than the foreign kind used for a limited number of fungis and this encourage to apply studies and researches in order to be used in new products . It was also clear from the study using the economic evaluation criteria compared with the evaluation results that the project is considered of high economic avail and this is considered to be a significant remark for the decision markers in economic and drug fields .